The lost valley: a feature programme for broadcasting - Tracey, Hugh; Tracey, Peggy (International Library of African Music, 1959)
Based upon the story of that part of the great Zambezi Valley in Southern Africa which has recently been submerged beneath the waters of the Kariba Dam.
Keywords: Kariba Dam (Zambia and Zimbabwe); Folk Songs; Ethnomusicology; Tonga (Zambezi people); Tsonga (African people); Drama; Tonga (Zambia); Kariba Dam; African Music